Massive Idiopathic Myocardial Calcification Associated With ANK2 Mutation of Uncertain Significance - Raiza Pontes Rodrigues; Ricardo Paulo de Sousa Rocha; Rainne André Siqueira; Germana Porto Linhares Almeida; Glauber Gean Vasconcelos; Hevila Romana Vieira de Farias; Laura Leite da Escóssia Marinho; Juan Alberto Cosquillo Mejía; João David de Souza Neto; Jefferson Luís Vieira (Annals of Internal Medicine: Clinical Cases)
Massive myocardial calcification is a rare condition for which both diagnosis and therapy are not clearly established in the literature. Although imaging features are often nonspecific, the combination of imaging pattern and clinical history may help determine the clinical implications of myocardial calcification. Here, we report a case of massive idiopathic calcification associated with a rare heterozygous ANK2 mutation of uncertain significance. Mutations in ANK2 are linked to abnormal regulation of intracellular sodium and calcium, predisposing patients to arrhythmias, but there is no description of myocardial calcification.